Pulmonary mucormycosis in an immunocompetent young female: a case report and literature review - Zhang, Xun; Wu, Zhenbin; Shao, Shifeng (Frontiers in Medicine, 2024)
Mucormycosis is considered a rare but highly lethal fungal infection, often occurring in patients with poorly controlled diabetes or immunosuppression. Pulmonary mucormycosis progresses rapidly and is often associated with pulmonary infarction and hemoptysis. In this case report, we presented a young, immunocompetent female patient with newly diagnosed diabetes who was diagnosed early with Rhizopus delemar infection through metagenomic next-generation sequencing. Despite early diagnosis, the infection progressed rapidly, invading the tracheal cartilage and upper mediastinal soft tissue, ultimately leading to the patient’s unfortunate demise.